(3eNJUQ ef cJH GdSjGSIs
(3ChdgG (B:s
(3ai aVd GdNdGaI hMceJgG bGd UGMH GdCMcGe GdSdWGfjI (B: (3GdEeGeI ehVhYI dNdGaI GdfHhI ai MQGSI GdOjf hSjGSI GdOfjG s
(3BNQgG (B:s
(3jfJgi HaUd (B: (3hdG jfHZi dSWGf Cf jhdi GdNWW GdcHGQ GdCMOGK GdUZGQ hBNQ eG ajg (B: (3GdQYjI YHjO jJcYdge GdYOd GdYOd eCdha hgh bhGe GdYde s
(3HgG fXGe GdJYbjHIs
(3LeY GdeDda eGOJg ef cJGH GdSjGSI ddeQGOi hGdeHgL ddKYGdHi hSQGL Gdedhc ddWQWhTis
(3hGdCMcGe GdSdWGfjI ddeGhQOi hGdSjGSI dGHf MRe hZjQ Pdcs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdSjGSI hGdGLJeGYs